Model Pembinaan Prestasi Olahraga Anggar di Bengkalis Fencing Club - Aldy Miftahul Rezki; Ramadi; Rusmanto (Pendidikan Kepelatihan Olahraga FKIP Universitas Riau, 2024)
This research is a descriptive qualitative study that aims to provide a detailed description of the athlete achievement coaching system at Bengkalis Fencing Club. Data was obtained through interviews with athletes, coaches, and club administrators. The results showed that the athlete recruitment system is running well, free of charge and open to the public, in accordance with the recruitment theory by Mulyati (2018) and Mustofa (2018). Physical and technical training programs are carried out regularly and systematically, in accordance with the training theory by Harsono (2017) and Purnomo (2019). The existing facilities and infrastructure are adequate but need to be improved, in line with the opinion of Hafidz (1989) in Sopian (2019). The achievements of Bengkalis Fencing Club athletes are high, with good mental preparation, as stated by Putri (2023). Recruitment of coaches is based on their qualifications and certifications, in accordance with the training theory by Suyono and Monalisa (2016). The club's organizational structure plays an optimal role in supporting athlete achievement, as stated by Rumpis Agus Sudarko (2009) in Umam (2017). Fund management is carried out by submitting SPJ to KONI and DISPORA, as well as proper planning, in accordance with the opinion of Agus Kristiyanto (2011). The overall results show that Bengkalis Fencing Club has a good coaching system but still needs improvement in several aspects.